Embedded systems - Kothari, D. P. 1944-; Vasudevan, Shriram K.; D., Sundaram R. M.; N., Murali (New Academic Science, 2015)
"In this book, the subject is developed from basics of components involved. Each concept is clearly depicted through illustrations. Programming has been carried out in C programming with Linux background which is simple and elegant. A set of interesting quiz and review questions has been presented at the end of each chapter which will enhance the understanding of the reader. The book Embedded Systems is a throng of various topics from the basic building blocks, design methodologies, modeling of embedded systems to layered approach in embedded systems, microcontrollers till date i.e., ARM controllers. The target of writing this book is to make the readers aware of what an embedded system is all about, how it is constructed, challenges faced in this field and coding for it. The reader who is totally new to this subject can definitely opt for this book to get a feel for this subject. Embedded System is present almost everywhere and it has occupied an inevitable place in the market. We, the consumers live with Embedded Systems all the way viz., watches, mobile phones, refrigerators, cars, music systems and what not ... In this book, every topic has been supported with practical examples. In addition to this, the programming concepts have been fully supported with simple and elegant C codes which have been executed in Linux OS as well. After every chapter, the reader is presented with a set of interesting quiz questions, which will provoke his/her thinking. In short, it will be good and friendly learning experience for the reader."--Amazon.in